Skeletal muscle proteomics: considerations and opportunities - Julian P. H. Wong; Yaan-Kit Ng; Jeppe Kjærgaard; Ronnie Blazev; Atul S. Deshmukh; Benjamin L. Parker (npj Metabolic Health and Disease)
Abstract Skeletal muscle accounts for 30–40% of body weight and plays an indispensable role in maintaining movement and is also a central regulator of whole-body metabolism. As such, understanding the molecular mechanisms of skeletal muscle health and disease is vital. Proteomics has been revolutionized in recent years and provided new insights into skeletal muscle. In this review, we first highlight important considerations unique to the field which make skeletal muscle one of the most challenging tissues to analyse by mass spectrometry. We then highlight recent advances using the latest case studies and how this has allowed coverage of the skeletal muscle temporal, fibre type and stem cells proteome. We also discuss how exercise and metabolic dysfunction can remodel the muscle proteome. Finally, we discuss the future directions of the field and how they can be best leveraged to increase understanding of human biology.